Citizenship and Civic Activity in Contemporary Bulgaria: (Non-) European Dimensions - Popinanov, Boris (Sociologija. Mintis ir veiksmas, 2015)
This paper presents some theses on the development of citizenship issues in Bulgaria in recent decades. A working notion of citizenship is proposed in correspondence with the modern achievements of the theory. The historical context of the concept is briefly outlined bringing forth the formulation of two major problems. The discourse of rights is analyzed as both a basis of and an internal limitation on developing contemporary citizenship framework. The Bulgarian case is considered through the prism of the pre-democratic heritage and the consequences of the democratic change to the modification of state-citizens relationship. The protest activity is proved to be the key manifestation of civic activism. In the light of this, two illustrating examples are provided so that the character, the direction, the depth and the main elementsof change can be traced. At the end, some conclusions on perspectives of citizenship are made.
Keywords: citizenship; citizens-state relationship; non-democratic citizenship; European integration; social passiveness; discourse of rights; protest activity